The Influence of Institutional Word Methods on the Beginning Reading Ability of Class I Students at SDN Kalibuntu - Siti Nurfadilah; Rina Yuliana; Lili Fajrudin (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to determine the effect of the institutional word method on the beginning reading ability of class I students at SDN Kalibuntu. The type of research used in this research is quantitative research with quasi-experimental methods. The population in this research is class I which consists of classes Ia and Ib at SDN Kalibuntu. In this study, two classes were used as samples. Class Ia is the control class and class Ib is the experimental class. The instruments used in this research include interviews, pretest, posttest and documentation. The research results show that the institutional word method can influence the beginning reading ability of class I students at SDN Kalibuntu. This can be seen through the results of the proposed hypothesis test. Hypothesis testing uses the t-test with a significance level α = 0.05 with degrees of freedom (n-2) namely 23. With the acceptance criterion Ha if tcountttable. Obtained 12.29702 2.069 thus Ha is accepted with a confidence level of 95%. This shows that there is an influence from the use of the institutional word method on the beginning reading abilities of class I students at SDN Kalibuntu in the 2023/2024 academic year.